Clinical profile comparison of cisatracurium and rocuronium in elective surgery - Meena, Reema; Jain, Priyanka; Rana, Divya; Verma, Indu; Chauhan, Sunil (DiscoverSys Inc., 2019)
Background: Most surgeries are carried out with ease using neuromuscular blocking agents. This study was aimed to compare the intubating dose of cisatracurium and rocuronium regarding the onset of action, clinical duration, recovery index, intubating conditions, efficacy, and safety in elective surgery.Method: 60 adult patients of American Society Anesthesiology (ASA) grade I & II, underwent elective laparoscopic surgery were randomized to receive either cisatracurium 0.1 mg/kg (Group C) or rocuronium 0.6 mg/kg (Group R). Neuromuscular monitoring was done using STIMPOD Xavant NMS450. Relaxogram interpretation was carried out for the onset of action, clinical duration, and recovery index.Results: Cisatracurium had significant longer onset (233.33±62.31 vs. 86.66±28.62 seconds, p <0.001) and significant longer clinical duration (40±3.56 vs. 27.46±2.14 minutes, p <0.001) than rocuronium. Recovery index was significantly longer in the cisatracurium group (12.23±1.54 vs. 8.30±1.80 minutes, p <0.001). Clinically acceptable intubating conditions were achieved in 180 seconds (C group) compared to 60 seconds in the R group. No untoward or adverse response and complications were distinguished in either group.Conclusion: Cisatracurium 0.1 mg/kg exhibited a slower onset of action than rocuronium 0.6 mg/kg and provided excellent intubating conditions in the majority of patients after 180 seconds. The clinical duration and recovery index were significantly longer in cisatracurium compared to rocuronium. Both are potent and safe agents with excellent cardiovascular stability.